1997
DOI: 10.1093/infdis/175.supplement_1.s189
|View full text |Cite
|
Sign up to set email alerts
|

National Immunization Days: Experience in Latin America

Abstract: Organization of national immunization days (NIDs) in all countries in Latin America in which polio was endemic has been one of the key elements that led to the interruption of the circulation of the wild poliovirus in 1991 from the Americas. National initiatives for control or elimination of measles using similar strategies have emerged from the successful organization of NIDs for polio eradication and lead the way to the eventual global eradication of this major killer of children. The major reasons for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…1,2 In many countries, SIAs have largely contributed to the 99% global reduction in the incidence of paralytic poliomyelitis observed since the 1988 launch of the GPEI. [2][3][4] Despite the central role of SIAs in eradication efforts, setbacks in the GPEI have been attributed to low-quality SIAs. 5 Target dates for eradication have repeatedly been pushed back and, at present, transmission of wild poliovirus remains endemic in Afghanistan, Nigeria and Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In many countries, SIAs have largely contributed to the 99% global reduction in the incidence of paralytic poliomyelitis observed since the 1988 launch of the GPEI. [2][3][4] Despite the central role of SIAs in eradication efforts, setbacks in the GPEI have been attributed to low-quality SIAs. 5 Target dates for eradication have repeatedly been pushed back and, at present, transmission of wild poliovirus remains endemic in Afghanistan, Nigeria and Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the UNAP staff said that they enjoyed the experience of being involved in the MDA because they were able to help their community and contribute in eliminating a disease. Other instances of staff morale being boosted through participation in control programmes have been reported from national immunization days for polio eradication (Olive et al, 1997) and in HIV control projects (Buvé et al, 2003;Walton et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that mass vaccination in urban centers with high levels of measles transmission could reduce measles incidence among nonvaccinated children in peri-urban centers [9]. The MS wanted to profit from the mobilization of human and financial resources linked to poliovirus NIDs without compromising polio eradication efforts, which had begun in 1997 [10]. Urban centers provided the necessary infrastructure to deliver large quantities of measles vaccine quickly and safely without compromising polio vaccination during NIDs.…”
Section: Methodsmentioning
confidence: 99%